Time-resolved synchrotron radiation circular dichroism spectroscopy - Auvray, François (2020)
Ultraviolet (UV) synchrotron radiation circular dichroism (SRCD) spectroscopy has made an important contribution to the determination and understanding of the structure of bio-molecules. In this thesis work, we demonstrate an innovative approach that we term time-resolved SRCD (tr SRCD), overcoming limitations of current broadband UV SRCD setups, which could enable access to ultrafast (down to nanoseconds) time scales. The tr-SRCD setup takes advantage of the natural polarisation of the synchrotron radiation emitted by a bending magnet to record broadband UV CD faster than any current SRCD setup, improving the acquisition speed from 10 mHz to 130 Hz and the accessible temporal resolution by several orders of magnitude. I propose several acquisition protocols that use the two different configurations of the the tr-SRCD setup. They would allow one to follow dynamics occurring on a time range spanning from tens of nanoseconds to minutes. I present results on camphorsulfonic acid (CSA) that allowed us to validate our methodology and also to assess the performance of the tr-SRCD setup. I illustrate the potential of the new approach for biological applications by following the concentration changes of isomers of the FK-11-X peptide after photoisomerisation. I point out the limitations of this approach and I propose an alternative method that should limit them. I present the results of our first tests that use this method and we compare them with standard SRCD and tr-SRCD spectra. I dedicate the last part of this thesis to a complementary study of the FK-11-X peptide via the both theoretical and experimental approaches. I present some molecular dynamics simulations and show that using the combination of experimental data acquired with the tr-SRCD setup coupled to first principles calculations of CD could facilitate the determination of transient structures between two stable conformations.